Bremsstrahlung converter system with target in vacuum; Vacuum; Vol. 187 - Egorov I. S. Ivan Sergeevich; Yu Xiao; Poloskov A. V. Artem Viktorovich; Serebrennikov M. A. Maksim Anatolevich; Le Xiaoyun; Remnev G. E. Gennady Efimovich (2021, 2021)
Title screen